PENGARUH IKLIM ORGANISASI, MOTIVASI KERJA DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI DI KANTOR WILAYAH DIREKTORAT JENDERAL PAJAK SUMATERA UTARA I - Kristina Romauli (JEKKP (Jurnal Ekonomi, Keuangan dan Kebijakan Publik), 2020)
The formulation of the problem in this research is how the influence of organization climate on employees  performance. How  influence of work motivation on employees  performance. How  influence of  work satisfaction on employees  performance. How  influence of  organization climate, work motivation and  work satisfaction on employees  performance. The purpose of this research is for know influence and analize of  organization climate on employees  performance. For know influence and analize of work motivation on employees  performance. For know influence and analize  work satisfaction on employees  performance. For know influence and analize organization climate, work motivation and  work satisfaction on employees  performance. The sample in this research is 95 employees, with data analysis technique used is multiple linear regression analyze. The results of this research explain that organization climate effect has a positive and significant on employee performance. Work motivation effect has a positive and significant on employee  performance. work satisfaction effect has a positive and significant on employee performance. Organization climate, work motivation and  work satisfaction effect  have a positive and significant on employee  performance.